HBV-associated DLBCL of poor prognosis: advance in pathogenesis, immunity and therapy - Wan, Xin; Young, Ken H.; Bai, Ou (Frontiers in Immunology, 2023)
Advanced studies have shown a biological correlation between hepatitis B virus (HBV) and B-cell lymphoma, especially diffuse large B-cell lymphoma (DLBCL). Patients with DLBCL infected with HBV (HBV-associated DLBCL) are clinically characterized by an advanced clinical stage, poor response to front-line immunochemotherapy regimens, and worse clinical prognosis. HBV-associated DLBCL often exhibits abnormal activation of the nuclear factor kappa B pathway as well as mutations in oncogenes, including Myc and BCL-6. Currently, there is no consensus on any specific and effective treatment for HBV-associated DLBCL. Therefore, in this review, we comprehensively and mechanistically analyzed the natural history of HBV infection and immunity, including HBV-mediated oncogenes, immune escape, epigenetic alterations, dysregulated signaling pathways, and potential therapeutic approaches for HBV-associated DLBCL. We hope that an improved understanding of the biology of HBV-associated DLBCL would lead to the development of novel therapeutic approaches, enhance the number of effective clinical trials, and improve the prognosis of this disease.